Physicians’ knowledge about pharmacovigilance in Iraq - RMS, Muhannad; YA, Arwa; QBA, Omer; Elkalmi, Ramadan Mohamed Mahmod; Kurmanji, Jaafer M (OMICS International, 2016)
Background: Pharmacovigilance plays an essential role in the reduction of adverse drugs reaction (ADRs), thus the evolution and growth of this science are critical for effective and safe clinical practice. Aim: This study will evaluate doctors’ attitudes, barriers and factors encouraging toward ADRs reporting. Methods: A cross-sectional prospective study has been conducted. It was a psychometric evaluation assessment using a previously modified questionnaire. Results: The majority of the surveyed doctors (78%) believed that reporting adverse drug reactions (ADRs) is part of their duty, and monitoring drug safety is also important (96%). The study findings revealed that about 68% of the doctors felt that they did not have sufficient clinical knowledge to detect ADRs. Nearly two-third of the doctor’s agreed that they are not convinced that the ADRs are caused by the drug. This study show that an association between doctors knowledge about ADRs detection and the number of patient seen by day, as the number of patient increased the doctors knowledge about ADRs improved. Recommendations: Special and direct educational programs, along with continued promotion, could help to enhance the involvement of physicians in ADR reporting and pharmacovigilance activities and help to reduce misconceptions and other logistic barriers to ADR reporting. Further studies with large populations are needed for a better understanding of the actual deterrents which prevent private clinic doctors from reporting ADRs.